Pemanfaatan Bahan Organik dalam Pembuatan Pupuk Kompos - Lalona, Ferdianto; Fatmawati, Fatmawati; Herawati, Kristiani; Afianti, Afifa Suci; Nur R, Nofa Safitri; Hartanto, Dimas; Zulkaidhah, Zulkaidhah; Toknok, Bau; Maiwa, Arman; Rahman, Abdul; Sofyan, Sofyan; Lamaniu, Moh Galang (Mitra prima, 2025)
Nutrient deficiency in soil has a negative impact on plant growth and productivity. Limited use of chemical fertilizers and poor soil conditions encourage the need for environmentally friendly alternatives. One solution is the utilization of organic waste such as goat manure, rice husks, and bran as raw materials for compost fertilizer. This training aimed to improve the knowledge and skills of SETMA members at the Faculty of Forestry, Tadulako University, in processing organic waste into quality solid fertilizer. The training was carried out in three stages: preparation, implementation, and evaluation. The implementation phase included theoretical sessions on nutrient content and material benefits, followed by hands-on practice in compost production, from mixing materials, fermentation using EM4, to storage. Evaluation was conducted through pre-tests, post-tests, and observation during practice. The results indicated increased understanding and active participation among participants. This training not only equipped them with technical skills but also raised awareness about the importance of managing organic waste to support sustainable agriculture. It is expected that this activity can be widely implemented and serve as a model for environmental education in both academic and community settings.